2015
DOI: 10.1016/j.neuron.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Instructing Perisomatic Inhibition by Direct Lineage Reprogramming of Neocortical Projection Neurons

Abstract: Summary During development of the cerebral cortex, local GABAergic interneurons recognize and pair with excitatory projection neurons to ensure the fine excitatory-inhibitory balance essential for proper circuit function. Whether the class-specific identity of projection neurons has a role in the establishment of afferent inhibitory synapses is debated. Here, we report that direct in vivo lineage reprogramming of layer 2/3 (L2/3) callosal projection neurons (CPNs) into induced corticofugal projection neurons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 42 publications
7
51
0
Order By: Relevance
“…qPCR (data not shown) and RNAseq data ( Fig. 4e) confirmed that purified CSN expressed markers typical of the cortical layer V subcerebral projection neurons, and did not express any marker typical of upper layer projection neurons 20,24,25 , and vice-versa ( Fig. 4e).…”
Section: Purification Of Adult Csn Under Healthy and Neurodegenerativmentioning
confidence: 66%
“…qPCR (data not shown) and RNAseq data ( Fig. 4e) confirmed that purified CSN expressed markers typical of the cortical layer V subcerebral projection neurons, and did not express any marker typical of upper layer projection neurons 20,24,25 , and vice-versa ( Fig. 4e).…”
Section: Purification Of Adult Csn Under Healthy and Neurodegenerativmentioning
confidence: 66%
“…The specialization of CPN subtypes is largely determined by their axonal outputs [30][31][32] . Thus, we asked if axonal targeting specificities of CPN subtypes were altered in absence of NeuroD2.…”
Section: Altered Relative Size Of Cortical Layers In Neurod2-deficienmentioning
confidence: 99%
“…Recent genome-wide transcriptome analyses of isolated converted neurons have demonstrated that, as in pancreatic ÎČ-cell conversion, converted neuron-like cells are not identical to endogenous neurons (Li et al, 2014; Ye et al, 2015). It is likely that the surrounding microenvironment/niche plays a key role in the maturation of converted cells.…”
Section: Regeneration In Non-mammalian Vertebrates and Other Mammamentioning
confidence: 99%